To Determine the Association between Endometrial Polyp and Metabolic Syndrome - Rasool, Saba; Raffique, Sidra; Bashir, Maria; Rauf, Abdul; Maqbool, Amna; Shaukat, Shysta (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Endometrial polyps are common among females especially in postmenopausal women. They have different type of prognosis and could lead to other related comorbidities. Metabolic syndrome is one of those conditions. Aim: To determine the association between endometrial polyp and metabolic syndrome. Study design: Case control study. Place and duration of study: Department of Obstetrics and Gynecology, Unit-IV, Sir Ganga Ram Hospital, Lahore from12-04-2016 to 13-10-2016. Methodology: One hundred women presenting in the obstetric and gynecological outdoor of Sir Ganga Ram Hospital, Lahore who meet the inclusion criteria of age between 18 to 60 years and with confirmation of endometrial polyps enrolled in this study. Detailed history and written informed consent was obtained from each patient. Two groups of patients were assimilated as follows. Cases: Those with endometrial polyp (as per operational definition), Controls: Healthy women without endometrial polyp (endometrial thickness≤5mm on transvaginal ultrasound scan). Patient’s workup was done on outdoor basis and demographic details along with presence/absence of metabolic syndrome were recorded in the attached proforma. All patients were examined by a single resident and all labs were acquired from a single (Hospital) laboratory to eliminate bias. Results: The mean age of the study participants was 33.57±6.65 years. The women who presented are maximum of having second parity 42(42%) and parity 3, 23(23%). There was significant difference for the metabolic syndrome in the cases and control as there were 33(62%) cases who have metabolic syndrome and 20(37%) control were having this disease.(odds ratio >1). Conclusion: There is significant association of endometrial polyps with metabolic syndrome